Regulatory considerations for vaccine development: talk 2 - clinical regulatory considerations 2 - Schrager, Lewis K. (Henry Stewart Talks, 2015)
Biological License Application (BLA) pathways, Traditional, accelerated approval, “Animal Rule”, Programs that accelerate the clinical testing (IND) and review (BLA) processes, Fast track designation, Breakthrough designation, Priority review, The package insert, Pediatric study requirements, Adjuvants, Adaptive trial design from a regulatory perspective, Developing vaccines for global infectious diseases